GLK transcription factors coordinate expression of the photosynthetic apparatus in Arabidopsis. - Waters, M; Wang, P; Korkaric, M; Capper, R; Saunders, N; Langdale, J (2009)
Chloroplasts of photosynthetic organisms harness light energy and convert it into chemical energy. In several land plants, GOLDEN2-LIKE (GLK) transcription factors are required for chloroplast development, as glk1 glk2 double mutants are pale green and deficient in the formation of the photosynthetic apparatus. We show here that glk1 glk2 double mutants of Arabidopsis thaliana accumulate abnormal levels of chlorophyll precursors and that constitutive GLK gene expression leads to increased accumulation of transcripts for antenna proteins and chlorophyll biosynthetic enzymes. To establish the primary targets of GLK gene action, an inducible expression system was used in combination with transcriptome analysis. Following induction, transcript pools were substantially enriched in genes involved in chlorophyll biosynthesis, light harvesting, and electron transport. Chromatin immunoprecipitation experiments confirmed the direct association of GLK1 protein with target gene promoters, revealing a putative regulatory cis-element. We show that GLK proteins influence photosynthetic gene expression independently of the phyB signaling pathway and that the two GLK genes are differentially responsive to plastid retrograde signals. These results suggest that GLK genes help to coregulate and synchronize the expression of a suite of nuclear photosynthetic genes and thus act to optimize photosynthetic capacity in varying environmental and developmental conditions.